Dyed in the wool? An empirical note on fan loyalty - Terry Robinson (The University of Manchester, Manchester Business School, 2009)
This paper attempts to investigate empirically the strength of intra-city football club support and seeks to test the commonly held belief among the sports community that supporters will not switch allegiance between city rivals very readily. To test this phenomenon data on the attendances of five English city rival clubs is used to conduct a cointegration analysis. The results imply that a stable relationship does not exist between the attendance series which throws doubt on the 'invariant support' hypothesis. To test the possibility that this result could be due to fickle supporters ceasing to attend, a sensitivity analysis is conducted between attendances and performance.
Keywords: 330; Fußballsport; Beziehungsmarketing; Konsumentenverhalten